1993
DOI: 10.1080/01140671.1993.9513740
|View full text |Cite
|
Sign up to set email alerts
|

Management of Triumph’ barley for high yield and malting quality on light soils in Canterbury, New Zealand

Abstract: This 4-year study was initiated to formulate a management package for producing high yields of high quality malting barley and involved large-scale trials comparing the levels and interactions of nitrogen (N), irrigation, and disease and pest control on yield and quality. One ha each of autumn and spring sown crops were sown in mid Canterbury each year. In the first 3 years, low and high levels of irrigation (flood irrigation when gravimetric soil moisture in the top 150 mm of soil fell to either 15% or 20%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…GNC varied by site location, with the Stradbally site producing significantly higher GNC values than the Bunclody site; however, GNU was also significantly greater at the Stradbally site. GNC increased progressively with greater increments of N as per the traditional relationship previously reported by others (Gately, 1971; Lord and Vaughan, 1987; Martin and Daly, 1993).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…GNC varied by site location, with the Stradbally site producing significantly higher GNC values than the Bunclody site; however, GNU was also significantly greater at the Stradbally site. GNC increased progressively with greater increments of N as per the traditional relationship previously reported by others (Gately, 1971; Lord and Vaughan, 1987; Martin and Daly, 1993).…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, in the Midwest region of the USA, Weston et al (1993) observed that delayed planting also reduced malt extract; however, most recently, O'Donovan et al (2016) reported that sowing date had little influence on malt quality under Canadian Prairie conditions. Other studies across different growing environments have reported detrimental effects of increased N application on malt extract (Martin and Daly, 1993;Weston et al, 1993). Edney et al (2012) also reported that increasing N application had a negative effect on malt extract but also on modification analyses such as Kolbach index and friability.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…s o w n b a r l e y (Cranstown 1992). The yield and grain quality (grain N and screenings) Previous work has also shown that increased N of spring malting barley ex-farm depends on season, application generally increases yield, grain N and the soil type and a large number of agronomic factors amount of screenings (Gately 1968;Garstang & including cultivar, sowing date, seed rate, place in Giltrap 1990;Cranstown 1992;Martin & Daly 1993), rotation, previous crop, amount of fertilizer N, timing although the application of high rates of N may of fertilizer N and disease control. All these factors reduce optimum yields and acceptability for malting are important both to the grower and the maltster in (Harrington et al 1975;Withers & Dyer 1990; terms of their effect on production and overall Bulman & Smith 1993).…”
Section: J Conrymentioning
confidence: 99%